Exploring the relationship between entrepreneurial orientation and ethics among Malaysian Women-owned MSMEs: A PLS analysis - Rashid, Umi Kartini; Lohana, Sonia; Nasuredin, Juzaimi; Abu Seman, Noor Aslinda; Mohamad, Arifha; Musa, Rusnifaezah (2024)
Entrepreneurship is vital for modern economies, with entrepreneurial orientation (EO) being key for micro, small and medium-sized enterprises (MSMEs) to thrive. This study addressed the literature gaps by examining the EO, ethics, and business performance in women-owned MSMEs in Malaysia, considering the gender variations. The ethical dimension’s role in influencing business performance was explored, leveraging the Partial Least Square (PLS) approach and data from 207 women-owned MSMEs. Three pivotal EO elements—risk-taking, proactiveness, and innovativeness—were identified through PLS regression analysis. The study enriched the literature by empirically probing connections between EO subcomponents, ethics, and business performance in underexplored Malaysian women-owned MSMEs. Findings underscored the critical role of EO and ethical practices in entrepreneurial success. Policymakers could glean valuable insights to develop supportive policies for women-owned MSMEs in Malaysia, emphasizing the need for user-friendly, consistent, and standardized policies across all MSMEs’ sectors. Overall, this research contributed to fostering entrepreneurship, ethical practices, and gender equality, indirectly impacting SDG 4 by providing practical insights into entrepreneurship that benefit the learning and development of MSMEs.